Evaluation of Different EEG Acquisition Systems Concerning Their Suitability for Building a Brain–Computer Interface: Case Studies - Pinegger, Andreas; Wriessnegger, Selina C.; Faller, Josef; Müller-Putz, Gernot R. (Frontiers in Neuroscience, 2016)
One important aspect in non-invasive brain-computer interface (BCI) research is to acquire the electroencephalogram (EEG) in a proper way. From an end-user perspective this means with maximum comfort and without any extra inconveniences (e.g., washing the hair). Whereas from a technical perspective, the signal quality has to be optimal to make the BCI work effectively and efficiently. In this work we evaluated three different commercially available EEG acquisition systems that differ in the type of electrode (gel-, water-, and dry-based), the amplifier technique, and the data transmission method. Every system was tested regarding three different aspects, namely, technical, BCI effectiveness and efficiency (P300 communication and control), and user satisfaction (comfort). We found that the water-based system had the lowest short circuit noise level, the hydrogel-based system had the highest P300 spelling accuracies, and the dry electrode system caused the least inconveniences. Therefore, building a reliable BCI is possible with all evaluated systems and it is on the user to decide which system meets the given requirements best.